Breakable mesoporous silica nanoparticles for targeted drug delivery. Issue 13 (14th March 2016) - Maggini, Laura; Cabrera, Ingrid; Ruiz-Carretero, Amparo; Prasetyanto, Eko A.; Robinet, Eric; De Cola, Luisa
Abstract : "Pop goes the particle". Here we report on the preparation of redox responsive mesoporous organo-silica nanoparticles containing disulfide (S–S) bridges ( ss -NPs ) that, even upon the exohedral grafting of targeting ligands, retained their ability to undergo structural degradation, and their increased local release activity when exposed to a reducing agent. Abstract : "Pop goes the particle". Here we report on the preparation of redox responsive mesoporous organo-silica nanoparticles containing disulfide (S–S) bridges ( ss -NPs ) that, even upon the exohedral grafting of targeting ligands, retained their ability to undergo structural degradation, and increase their local release activity when exposed to a reducing agent. This degradation could be observed also inside glioma C6 cancer cells. Moreover, when anticancer drug-loaded pristine and derivatized ss -NPs were fed to glioma C6 cells, the responsive hybrids were more effective in their cytotoxic action compared to non-breakable particles. The possibility of tailoring the surface functionalization of this hybrid, yet preserving its self-destructive behavior and enhanced drug delivery properties, paves the way for the development of effective biodegradable materials for in vivo targeted drug delivery.